2016
DOI: 10.1126/science.aaf7943
|View full text |Cite
|
Sign up to set email alerts
|

Early Neolithic genomes from the eastern Fertile Crescent

Abstract: We sequenced Early Neolithic genomes from the Zagros region of Iran (eastern Fertile Crescent), where some of the earliest evidence for farming is found, and identify a previously uncharacterized population that is neither ancestral to the first European farmers nor has contributed substantially to the ancestry of modern Europeans. These people are estimated to have separated from Early Neolithic farmers in Anatolia some 46,000 to 77,000 years ago and show affinities to modern-day Pakistani and Afghan populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
229
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(265 citation statements)
references
References 135 publications
17
229
1
2
Order By: Relevance
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%
“…In this study, the authors suggested that the affinities of Zagros Neolithic individuals to modern pop- ulations of southern Asia can be related to the spread of Indo-Iranian languages or Dravidian languages, along with the demographic expansion of farming into the region (Broushaki et al 2016). This study also pointed out that the European Neolithic migration probably had a different genetic source than the eastern Fertile Crescent.…”
Section: Four Early Neolithic (En) Genomes From Zagros Inmentioning
confidence: 80%
“…Iran show a distinct genetic signature from both European hunter-gatherers and farmers, close to modern Pakistanis and Afghans (Broushaki et al 2016). In this study, the authors suggested that the affinities of Zagros Neolithic individuals to modern pop- ulations of southern Asia can be related to the spread of Indo-Iranian languages or Dravidian languages, along with the demographic expansion of farming into the region (Broushaki et al 2016).…”
Section: Four Early Neolithic (En) Genomes From Zagros Inmentioning
confidence: 89%
See 2 more Smart Citations